Pentahelix Collaboration Approach in Disaster Management: Case Study on Disaster Risk Reduction Forum-East Java - Windiani, Windiani (Institut Teknologi Sepuluh Nopember, 2020)
This article aims to describe the implementation of the pentahelix collaboration approach on disaster management in East Java. The research problem is how the pentahelix collaboration approach was developed by Disaster Risk Reduction Forum in East Java? This study uses a qualitative method, while data collection uses a focus group discussion and participant observation. The finding research showed that the pentahelix collaboration consists of Government, Academics, Community, Business and Media. They have a commitment to collaboration for reducing disaster risk in East Java region which was categorized as a natural disaster-prone area. Besides that, this is considered strategic to be developed in industrial revolution 4.0 era which requires fast information technology, networking and sustainable-collaboration. An interesting findings research is the application of an inclusive approach by involving the disabled community in Disaster Risk Reduction Forum activity.